Letrozole versus laparoscopic ovarian drilling in clomiphene citrate-resistant women with polycystic ovary syndrome: a systematic review and meta-analysis of randomized controlled trials - Qiong Yu; Shifu Hu; Yingying Wang; Guiping Cheng; Wei Xia; Changhong Zhu (BMC, 2019)
Abstract The objective of this systematic review was to examine the literature and to compare the effectiveness of letrozole (LE) versus laparoscopic ovarian drilling (LOD) for the induction of ovulation in women with clomiphene citrate (CC)-resistant polycystic ovary syndrome (PCOS). The PUBMED, Web of Science, and EMBASE databases were searched systematically for eligible randomized controlled trials (RCTs) from English language articles published from database inception to September 2018. Data were independently extracted and analyzed using the fixed-effects model or random-effects model according to the heterogeneity of the data. Four RCTs including 621 patients (309 in the LE group and 312 in the LOD group) met the inclusion criteria. There were no differences with regard to ovulation rate (relative risk [RR] 1.12; 95% confidence interval [CI] 0.93 to 1.34; P = 0.12, I2 = 90%, 541 patients, three studies), pregnancy rate (RR 1.21; 95% CI 0.95 to 1.53; P = 0.12, I2 = 0%, 621 patients, four studies), live birth rate (RR 1.27; 95% CI 0.96 to 1.68; P = 0.09, I2 = 19%, 541 patients, three studies), and abortion rate (RR 0.7; 95% CI 0.3 to 1.61; P = 0.40, I2 = 0%, 621 patients, four studies) between the two groups. These results indicated that LE and LOD appear to be equally effective in achieving live birth rate in patients with CC-resistant PCOS.